2002
DOI: 10.1126/science.1066611
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Surface Control of Organic Carbon in Black Shale

Abstract: We show that 85% of variation in total organic carbon can be explained by mineral surface area in a black shale deposit from two locations in the late Cretaceous Western Interior Seaway, United States. This relation suggests that, as in modern marine sediments, adsorption of carbon compounds onto clay mineral surfaces played a fundamental role in the burial and preservation of organic carbon. Our data also provide evidence for organic matter within the smectite interlayer. This association implies that organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
220
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(232 citation statements)
references
References 21 publications
8
220
1
3
Order By: Relevance
“…The content of the interlayer organics accounted for approximately 25-50 wt.% of the total extracted organics, which indicates the significance of the interlayer organics in resource assessments. Kennedy et al (2002) also found that organic matter was sequestered within the interlayer space of smectite clay in Cretaceous black shale. Moreover, experimental study indicated that some organic constituents, who are of importance in petroleum generation, can enter into the interlayer space of clay minerals.…”
Section: Introductionmentioning
confidence: 91%
“…The content of the interlayer organics accounted for approximately 25-50 wt.% of the total extracted organics, which indicates the significance of the interlayer organics in resource assessments. Kennedy et al (2002) also found that organic matter was sequestered within the interlayer space of smectite clay in Cretaceous black shale. Moreover, experimental study indicated that some organic constituents, who are of importance in petroleum generation, can enter into the interlayer space of clay minerals.…”
Section: Introductionmentioning
confidence: 91%
“…Kennedy et al (2002) reported that organic 14 carbon controls the orientation of mineral surfaces in black shales. Therefore, clay mineral formation by bacteria is linked with the adhesive nature of surface materials that leads to inflated spherules or "clay bubbles".…”
Section: Biomineralization Of Halloysite On Microbes At Ph 6-7mentioning
confidence: 99%
“…Many organic compounds can be adsorbed onto surfaces and into the interlayer regions, in some cases forming weak bonds with phyllosilicate surfaces. Adsorption of organic molecules into the interlayer region is particularly important for very low molecular weight compounds, such as amino acids (Hedges & Hare, 1987) and polysaccharides (Dontsova and Bigham, 2005) as well as higher molecular weight material (Mayer, 1994a, b;Kennedy, et al, 2002). Organic molecules compete with other polar species in the environment (e.g., water, cations, etc.)…”
Section: Distribution and Importance Of Phyllosilicates For Habitabilmentioning
confidence: 99%